Weeds of Rice in West Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Weeds are the major biological problem in rice production. This bilingual guide, in English and French, with colour photographs and illustrations, helps to identify the major weed species, as well as some fallow and occasional weeds, and provides...